The current quality of Svetozar Marković’s views of “socialism and the social question” - Vratuša, Vera (Sociološki pregled, 2026)
The paper presents the understanding of the social and societal questions, i.e., of the social revolution in Svetozar Marković’s work, as a collection of articles summarizing the basic theses of all important works by Marković, from the Program for the paper Radenik (Worker), via Serbia in the East, the articles about women’s equality, the Paris Commune and education, to Greater Serbia. Due to the limited space. The focus of this paper will be the analysis of those articles which most directly refer to Marković’s development of the concept of socialism through a critical dialogue with the perceptions of socialism and democracy in the articles of Vladimir Jovanović as the most prominent representative of liberalism among the members of the Association of Serbian Youth. In the conclusion, the author sums up the current quality of the views of socialism and the social question of the most important Serbian socialist of the 19th century, relevant for understanding the success and/or failure to fulfil the first basic item of Marković’s “political will” in reference to the internal aspects of socialism and social revolution in the Principality of Serbia and in the Balkans. Due to the limited space, the second item of Marković’s “will”, i.e., the revolution in Turkey and the federation on the Balkan Peninsula, will be discussed in a separate text.
Keywords: Svetozar Marković (1846–1875); socialism; social questions